Differential Causal Associations of Chronic Gastritis and Ulcerative Colitis with Melanoma Risk: A Mendelian Randomization Study Using Large-Sample GWAS Data - Jin R; Lu J; Cheng S; Shi S (Clinical, Cosmetic and Investigational Dermatology, 2025)
Ruiqi Jin,1,* Jiamin Lu,1,* Shile Cheng,2 Shupeng Shi3 1Department of Plastic Surgery, The First Affiliated Hospital of Sun Yat-Sen University, Guangzhou, 510080, People’s Republic of China; 2Department of Plastic and Reconstructive Surgery, Shenzhen Qianhai Taikang Hospital, Shenzhen, 518000, People’s Republic of China; 3Department of Plastic Surgery, the First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, 230001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ruiqi Jin, Department of Plastic Surgery, The First Affiliated Hospital of Sun Yat-sen University, Guangzhou, 510080, People’s Republic of China, Email dr_jinruiqi@163.com Shupeng Shi, Department of Plastic Surgery, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, 230001, People’s Republic of China, Email doctorshishupeng@163.comPurpose: Chronic inflammatory diseases are thought to influence cancer development through systemic inflammation and immune dysregulation. However, the causal relationship between chronic gastrointestinal inflammation and cutaneous melanoma remains unclear. This study employed Mendelian randomization (MR) to investigate the potential causal link between chronic gastrointestinal inflammatory diseases and melanoma risk.Patients and Methods: Genetic variants associated with chronic gastrointestinal inflammation were derived from large-scale genome-wide association studies (GWAS) on autoimmune hepatitis, chronic gastritis, chronic hepatitis B and C infections, chronic pancreatitis, Crohn’s disease, gastroesophageal reflux disease, and ulcerative colitis. Melanoma GWAS data served as the outcome dataset. A two-sample MR analysis was conducted to assess causal relationships, with inverse variance weighting (IVW) as the primary method. Sensitivity analyses, including MR-Egger, MR PRESSO, and Cochran’s Q test, were also performed.Results: The MR analysis revealed a significant inverse causal relationship between chronic gastritis and melanoma risk (p = 0.023, OR = 0.630, 95% CI = 0.422– 0.939). In contrast, a positive causal association was found for ulcerative colitis, with the IVW method showing a significant increase in melanoma risk (p = 0.014, OR = 1.130, 95% CI = 1.025– 1.246). No significant causal relationships were observed for other inflammatory diseases, including autoimmune hepatitis, chronic hepatitis B/C, chronic pancreatitis, Crohn’s disease, and gastroesophageal reflux disease (all p > 0.05). Sensitivity analyses confirmed the robustness of these findings. Cochran’s Q test indicated no significant heterogeneity among genetic instruments for chronic gastritis or ulcerative colitis. The MR-Egger intercept test showed no evidence of horizontal pleiotropy, and the MR-PRESSO method identified no outlier SNPs. Leave-one-out analysis further demonstrated that no single SNP disproportionately influenced the results.Conclusion: This study provides evidence of an inverse causal relationship between chronic gastritis and melanoma risk. In contrast, ulcerative colitis was found to have a positive causal effect on melanoma susceptibility. These findings highlight the distinct roles that gastrointestinal inflammation may play in the pathogenesis of skin cancer, potentially mediated by divergent immune and inflammatory mechanisms.Keywords: Mendelian randomization, melanoma, chronic gastritis, ulcerative colitis, genetic variants